Ecografía pulmonar versus Radiografía de tórax como prueba diagnóstica para Neumonía adquirida en la Comunidad en Preescolares - Mendez Neciosup, Paola Lizeth (2022)
Pediatric Community-Acquired Pneumonia is a health problem associated with a high rate of morbidity and mortality. Although its diagnosis in children is clinical, imaging studies are commonly used to facilitate timely diagnosis and early treatment. Chest X-ray is used as first line. However, recently, lung ultrasound has gained importance and has promoted research in the pediatric field, as it is an easy-to-perform, non-invasive study with no risk of irradiation for patients. Objective: To determine the sensitivity and specificity of PE and CXR as a diagnostic test for CAP in preschool children. Methodology: A cross-sectional analytical observational study of Comparison of tests or diagnostic tests will be carried out.